The Effect of Personal Cost and Bystander Effect As Moderating Variable on Whistleblowing Intention - Christa Alethea; David Adechandra Ashedica Pesudo, S.E., M.Ak (Politeknik Negeri Madiun, 2021)
This study aims to determine the effect of personal cost on whistleblowing intention with the bystander effect as a moderating variable. The population in this study were students of the Faculty of Economics and Business, W University who are active in organization. The data analysis technique used is moderated regression analysis. The result of this study indicate that personal cost has a negative effect on whistleblowing intention and bystander effect has a negative effect which strengthens the negative effect of personal cost on whistleblowing intention.